Phytophthora ramorum and Phytophthora kernoviae on naturally infected asymptomatic foliage - Denman, S.; Kirk, S. A.; Moralejo, E.; Webber, J. F. (EPPO Bulletin, 2009)
Phytophthora ramorum and Phytophthora kernoviae are recently discovered invasive Phytophthoras causing leaf necrosis and shoot tip dieback mostly on ornamental and forest understorey species, but also cause bleeding cankers on stems of a wide range of tree species. Sporulation occurs only on infected shoots or fruits and foliage so foliar hosts are central to the disease epidemiology. In field trials to assess infection in trap plants exposed to natural inoculum of P. ramorum and P. kernoviae on rhododendron in south west England, it was discovered that leaves of the trap plants (Rhododendron‘Cunninghams White’) and holm oak (Quercus ilex) were asymptomatically infected and supported sporulation of both pathogens. More than half the rhododendron trap plants exposed to inoculum of P. kernoviae became infected compared with approximately a third of those exposed to P. ramorum in a natural situation. Approximately one third of the infections were detected from asymptomatic foliage for both pathogens. The significance of these findings for plant health regulation based on visual inspection as a measure to prevent introduction and dissemination of both these pathogens is explored and research gaps identified.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: asymptomatic infection; pathogen sporulation (voyant); Phytophthora kernoviae; Phytophthora ramorum

Phytophthora ramorum on Quercus ilex in the United Kingdom. - Denman, S.; Kirk, S. A.; Brasier, C. M.; Barton, V. C.; Hughes, K. J. D.; Webber, J. F. (PLANT DISEASE, 2005)
Phytophthora ramorum causes bleeding cankers of trunks of trees native to the west coast of the United States (i.e., Quercus kelloggii, Q. parvula var. shrevei, and Lithocarpus densiflorus). In the United Kingdom so far, bleeding cankers caused by inner bark infections have been found on Aesculus hippocastanum, Fagus sylvatica, Q. cerris, Q. falcata, and Q. petraea (http://rapra.csl.gov.uk [2005]). Shoot tip dieback (ramorum dieback) and foliar necrosis (ramorum leaf blight) are other diseases caused by the pathogen on understory and ornamental plants (3). Inoculum is produced on infected shoots and leaves of foliar hosts but not on bole cankers (1). Foliar hosts are thus critical in initiating and maintaining epidemics of tree mortality resulting from lethal bark cankers. Ramorum dieback and blight occurs in Europe on genera Rhododendron, Camellia, Kalmia, Pieris, and Viburnum (http://rapra.csl.gov.uk [2005]), and now we report these diseases on foliage and shoots of holm oaks (Quercus ilex) in Cornwall (UK). First discovered in November 2003, infected young leaves had a water-soaked, dull gray appearance, and petioles were blackened. Lesions started at leaf margins, tips, or petioles, often progressing into the midrib veins. Initial infections also occurred on shoots and extended into the petioles. If shoots were infected, they were blackened at first, but later in the season clusters of dry, dead leaves and twigs characterized branch tips. Infected mature leaves bore dry, reddish-brown, restricted lesions. P. ramorum (A1 sexual compatibility type belonging to the European population) was isolated and confirmed by morphological studies, ITS sequence (GenBank Accession No. AY924253), and amplified fragment length polymorphism analyses. Lesions developed on detached leaves dipped for 10 sec in inoculum (4 × 105 zoospores per ml) and incubated in moist chambers at 20°C for 6 days (2). Two isolates were used (four leaves per isolate). The pathogen was reisolated, and the tests were repeated twice. Koch's postulates were also successfully completed once on foliage attached to saplings. To our knowledge, this is the first report of P. ramorum on holm oak. So far, at least 24 holm oaks are infected at various woodland and garden sites in the United Kingdom; infected rhododendrons have also been found at these sites. P. ramorum has also been recorded on saplings in nurseries. The high sporulation potential, the evergreen nature of leaves, and susceptible shoots indicate that holm oak could be a significant source of inoculum for other hosts.
APSAPSThe following values have no corresponding Zotero field: pub-location: 3340 PILOT KNOB ROAD, ST PAUL, MN 55121 USA publisher: AMER PHYTOPATHOLOGICAL SOC
Keywords: pathogens; Phytophthora ramorum; Quercus ilex